PENGGUNAAN CORN GLUTEN MEAL SEBAGAI SUMBER PROTEIN PAKAN IKAN BANDENG (Chanos chanos) - Papap Farid Hakim; Achmad Noerkhaerin Putra; Mas Bayu Syamsunarno (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2022)
Feed is the main component in the cultivation of milkfish. The purpose of this study is to evaluate the effect of Corn Gluten Meal (CGM) as a protein source in the diet on the growth performance of milkfish. This research was conducted experimentally with initial milkfish weight of 4.9 ± 1.24 g/fish obtained from milkfish farmers on the north coast of Banten. The study design used a completely randomized design with five different treatments of CGM levels (0%, 25%, 50%, 75% and 100% CGM) and 4 replications were used in this study. Milkfish are kept in an aquarium (60 x 40 x 60 cm) with a density of 15 individuals/aquarium for 50 days. The results showed that the best value of feed efficiency, specific growth rate, and protein effiency ratio were obtained in CGM 75% treatment than the other treatments. The use of CGM in feed also had no effect (P> 0.05) on the survival rate of the milkfish. CGM can be used as proteon source in milkfish feed.